Summaries of cases dealt with by the almoner - Brimmell, Maud E.
1903-09-28 1903 1900s 5 pages 1. 11 mths f.v. A.B. girl of 20 suffering with early spinal caries box worker - Com. refused support ordered as unlikely to be persevered with & useless in present surroundings. A friendly interest in the girl shewed her real difficulties, & after a time she was induced to try service in the country the jacket having been supplied. After a plucky trial the plan failed, & the girl had to return to her old work, but so soon as opportunity occurred the she obtained for herself out door work & can now at the end of a year report herself as able to do without her support - the disease entirely arrested. 2 f.v. 11 mths E.N. child of 2 1/2 - one of four - suffering from insufficient nourishment - f. out of work. The child was referred to the parish D - but interest was kept up in the family - F. proved to be handy at gardening & to have a good reference from a member of the L.C.C. so was advised to apply to Parks Co. of L.C.C. the Vicar & others giving him what odd work they could. At the end of nearly a year he reports that he has temporary work with a good prospect of regular work on L.C.C. & is granted a small loan for boots &c. 3 Dec. 1902 Still in hand. f.v. M.H. 15. - girl of immoral tendencies - sent by respectable old country parents to be under the influence of married sister in London, where she speedily goes from bad to worse. An experienced rescue worker visits & gains the entire confidence of the sister. The girl is admitted to special Hos. for a short time - then temporarily in a small home till her friend has gained 378/IMSW/A/1/2/44